2009
DOI: 10.1093/nar/gkp741
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p54(nrb), a PSF partner protein, in DNA double-strand break repair and radioresistance

Abstract: Mammalian cells repair DNA double-strand breaks (DSBs) via efficient pathways of direct, nonhomologous DNA end joining (NHEJ) and homologous recombination (HR). Prior work has identified a complex of two polypeptides, PSF and p54(nrb), as a stimulatory factor in a reconstituted in vitro NHEJ system. PSF also stimulates early steps of HR in vitro. PSF and p54(nrb) are RNA recognition motif-containing proteins with well-established functions in RNA processing and transport, and their apparent involvement in DSB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 49 publications
9
78
0
Order By: Relevance
“…Since then, diverse studies have described it as a protein with pleiotropic functions mainly involved in RNA processing and transport, as well as a transcription factor (27). It has been implicated in diverse pathways, such as nuclear receptor signaling (35), DNA repair (36,37), and viral infection (38). Here we have shown that it can directly activate the p16-Ink4A locus, an important regulator of the G1 exit checkpoint of the cell cycle.…”
Section: Discussionmentioning
confidence: 69%
“…Since then, diverse studies have described it as a protein with pleiotropic functions mainly involved in RNA processing and transport, as well as a transcription factor (27). It has been implicated in diverse pathways, such as nuclear receptor signaling (35), DNA repair (36,37), and viral infection (38). Here we have shown that it can directly activate the p16-Ink4A locus, an important regulator of the G1 exit checkpoint of the cell cycle.…”
Section: Discussionmentioning
confidence: 69%
“…In the current study we found that overexpression of HLXB9 in mouse insulinoma MIN6 ␤-cells (containing normal endogenous menin), a condition that coincides with apoptosis, showed reduced level of transfected Nono protein. It has been previously noted that Nono is also down-regulated in melanoma cells undergoing apoptosis where Nono acts as a survival factor promoting a response to counteract apoptosis (24,25,43). Therefore, it appears that ectopic Nono expression is not tolerated in cells undergoing HLXB9-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was performed for 40 cycles in an Eppendorf Mastercycler Gradient (Eppendorf, Hamburg, Germany): 94 for 1 min, 55 for 1 min, and 72 for 1 min. ␤-Actin primers (sense 5=-AGTCCTGTGGCATCCAC-GAAACTA and antisense ACTGTGTTGGCGTACAGGTCTTTG) were used as internal standard (13). The PCR products were analyzed on 1.5% agarose gel and stained with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%